First findings of Otoceras (Ceratitida) in the Kobyuma zone of the Southern Verkhoyansk region, Northeastern Russia - R.V. Kutygin; I.V. Budnikov; A.S. Biakov; V.I. Davydov; A.N. Kilyasov; V.V. Silantiev (Учёные записки Казанского университета: Серия Естественные науки)
The samples of the genus Otoceras, which is an important biostratigraphic marker of the Permian-Triassic boundary deposits of the Boreal realm, were found in the Kobyuma structural and facies zone of the Southern Verkhoyansk region. The features of the geographic and vertical distribution of Otoceras in the northern part of the Southern Verkhoyansk region were considered. The age of Otoceras beds was discussed. In the Verkhoyansk region, the Otoceras beds are divided into Concavum and Boreale zones. In the Tiryakh-Kobyume section of the Kobyuma zone, two close levels with ceratites of the genus Otoceras were revealed. From the first (lower) level, Otoceras aff. gracile Tozer and O. sp. were identified, presumably related to the Concavum zone of the highest part of the Changhsingian stage (Permian, Lopingian Series). At the second (upper) level, a large specimen of the species Otoceras boreale Spath was discovered, which makes it possible to attribute the host deposits to the Boreale zone of the Induan stage base (Lower Triassic). A section interval containing ceratites of the genus Tompophiceras of the Pascoei and Morpheos zones was revealed above the Otoceras beds. Since no own Triassic local stratigraphic scheme has been established in the Kobyuma zone, it is expedient to use the Nekuchan Formation (Induan deposits) of the Allakh-Yun’ zone of the Southern Verkhoyansk region.